1994
DOI: 10.1128/mcb.14.11.7569
|View full text |Cite
|
Sign up to set email alerts
|

Identification of ETS domain proteins in murine T lymphocytes that interact with the Moloney murine leukemia virus enhancer.

Abstract: The enhancer of Moloney murine leukemia virus (Mo-MuLV) contains an array of transcriptional control elements that direct viral gene expression in diverse cell types. The murine transcription factor Ets-1 was shown to bind to the LVb and LVc elements of the enhancer by DNase I protection and methylation interference assays. Enhancers containing disrupted Ets-1 binding sites were tested in transient expression assays in the murine T-cell line EIA.El; alterations in the LVb element affected constitutive enhancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
55
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(58 citation statements)
references
References 58 publications
(61 reference statements)
3
55
0
Order By: Relevance
“…Specific hydration might therefore evolve as compensatory mechanism to replace some of the "missing" anhydrous contacts. The involvement of specifically bound water at the backbone contacts by PU.1 is also consistent with the substantially smaller DNA curvature (8°) compared with Ets-1 (27°) and GABP␣ (18°) despite sharing identical phosphate contacts (25). Finally, high affinity binding for the minimal ETS domain of Ets-1 exhibits dissociation constants at 10 Ϫ12 M under physiological conditions (43).…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…Specific hydration might therefore evolve as compensatory mechanism to replace some of the "missing" anhydrous contacts. The involvement of specifically bound water at the backbone contacts by PU.1 is also consistent with the substantially smaller DNA curvature (8°) compared with Ets-1 (27°) and GABP␣ (18°) despite sharing identical phosphate contacts (25). Finally, high affinity binding for the minimal ETS domain of Ets-1 exhibits dissociation constants at 10 Ϫ12 M under physiological conditions (43).…”
Section: Discussionsupporting
confidence: 64%
“…Specifically, the TTCC strand shows a strongly hypersensitive band at N 1 (5Ј-TpTpCpCpN 1 2pN 2 pT-3Ј) just 3Ј to the core consensus. This hypersensitivity is a universal hallmark of sequencespecific ETS-DNA complexes (22)(23)(24)(25)(26). It is attributed to a widening of the minor groove by the recognition helix (h3) at the major groove of the core consensus.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there may be auxiliary positive and negative regulatory elements between nucleotides k143 and k43, these data suggests that the element(s) primarily necessary for serum-induced ET-1 transcription lies within the first 43 bp of 5h-flanking promoter sequence. In scanning this sequence, a few possible binding sites for known transcription factors were found, including LVc, TCF-1 and GMCSF-CS sites [38][39][40][41][42][43]. However, these factors have only been found in T-and Blymphocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have indicated that promoter-defined Elf-1 sites from different genes bind preferentially different forms of Elf-1. The human IL-2 promoterdefined Elf-1 site binds all forms of Elf-1 (14), whereas the enhancer of the Moloney murine leukemia virus binds the 98-kDa form of Elf-1 (15).…”
Section: S Ystemic Lupus Erythematosus (Sle)mentioning
confidence: 99%